Exploring the Impact of Waterfront Street Environments on Human Perception - Yiqing Yu; Gonghu Huang; Dong Sun; Mei Lyu; Dewancker Bart (Buildings)
Urban waterfront streets are important mediators that reflect a city’s image and characteristics. They play a positive role in enhancing residents’ cohesion, mental and physical health, and social interactions. Human perceptions represent individuals’ psychological experiences and feelings toward the surrounding environment. Previous studies have explored the impact of urban street-built environmental factors on perceptions; however, research focusing on waterfront street environments and their impacts on human perceptions remains limited. Therefore, exploring the specific impact of waterfront street environmental characteristics on different dimensions of human perception is essential for guiding the development of livable cities. Based on Street View images (SVIs), this study applied artificial neural networks and machine learning semantic segmentation techniques to obtain physical feature data and human perception data of the Murasaki River waterfront line spaces in Kitakyushu, Japan. In addition, correlation and regression analyses were conducted to explore the specific impact of physical features on different dimensions of human perception in waterfront line spaces, and corresponding optimization strategies were proposed. The results show that street greenness significantly enhances perceptions of safety, wealth, and beauty, while effectively reducing boredom and depression. Furthermore, the building visual ratio contributes to increased street vitality. On the other hand, physical features such as openness, spatial indicators, and environmental color diversity have negative effects on positive perceptions, including safety and vitality. In particular, openness significantly increases boredom and depression. This study advances the exploration of urban waterfront street environments from the perspective of human perception, providing a theoretical foundation for improving the spatial quality of waterfront streets and offering references for human-centered urban planning and construction.